ChemInform Abstract: Synthetic Access to Poly‐Substituted 11H‐Pyrido[3, 2‐a]carbazoles, a DNA‐Intercalating Ellipticine Related Structure, and Their Antiproliferative Activity. Issue 45 (23rd October 2014) - Inokuchi, Tsutomu; et al., et al.
Abstract A facile access to polysubstituted pyridocarbazole derivatives is described using Fischer indole cyclization on 5‐oxo‐tetrahydroquinoline‐3‐carboxylate (I) followed by aromatization.